Chloride ion-doped polypyrrole nanocomposite as cathode material for rechargeable magnesium battery. (May 2018) - Zhao, Xiangyu; Zhao, Zhigang; Miao, Yingchun
Graphical abstract: Highlights: Chloride ion-doped polypyrrole nanocomposite is firstly developed as new cathode for rechargeable magnesium battery. Reversible redox reactions of nitrogen species in nanostructured polypyrrole in RMB system are proved. More than 95 mAh g −1 capacity and a high Coulombic efficiency of about 96% are delivered. Abstract: We report a chloride ion-doped polypyrrole/carbon nanotube (PPyCl/CNTs) nanocomposite as new cathode material for rechargeable magnesium battery. The PPyCl/CNTs nanocomposite with amorphous structure, uniform chlorine distribution and large specific surface area shows reversible electrochemical energy storage upon redox reaction of nitrogen species. The structural configuration of PPyCl by the incorporation of CNTs contributes to significant improvement in the electrochemical performance. More than 95 mAh g −1 capacity and a high Coulombic efficiency of about 96% are delivered. This study offers a promising way for designing new cathode for rechargeable magnesium batteries.